A caching file system for a programmer's workstation - Schroeder, Mike; Gifford, David K.; Needham, Roger M. (Proceedings of the 10th ACM Symposium on Opeating Systems Principles, 1985)
This paper describes a file system for a programmer's workstation that has access both to a local disk and to remote file servers. The file system is designed to help programmers manage their local naming environments and share consistent versions of collections of software. It names multiple versions of local and remote files in a hierarchy. Local names can refer to local files or be attached to remote files. Remote files also may be referred to directly. Remote files are immutable and cached on the local disk. The file system is part of the Cedar experimental programming environment at Xerox PARC and has been in use since late 1983.